2022
DOI: 10.1016/j.jvssci.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of von Willebrand factor in venous thromboembolic disease

Abstract: Objective Evolving evidence of the shared risk factors and pathogenic mechanisms in arterial and venous thrombosis questions of the strict vascular dichotomy of arterial vs venous. The connection between arterial and venous thrombosis has been highlighted by common underlying inflammatory processes, a concept known as thromboinflammatory disease. Using this relationship, we can apply knowledge from arterial disease to better understand and potentially mitigate venous disease. A protein that has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 124 publications
(144 reference statements)
0
8
0
Order By: Relevance
“…A number of other studies have suggested that VWF is associated with TEEs. [24][25][26] For example, the prospective LITE study, 26 which included 19,237 patients aged 45-64 years, who experienced a total of 159 venous thromboembolisms (VTEs), found a dosedependent relationship between plasma VWF levels and risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other studies have suggested that VWF is associated with TEEs. [24][25][26] For example, the prospective LITE study, 26 which included 19,237 patients aged 45-64 years, who experienced a total of 159 venous thromboembolisms (VTEs), found a dosedependent relationship between plasma VWF levels and risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did subsequently appear to show a higher increase in VWF:RCo activity and VWF antigen levels compared with patients who did not develop PE. A number of other studies have suggested that VWF is associated with TEEs 24–26 . For example, the prospective LITE study, 26 which included 19,237 patients aged 45–64 years, who experienced a total of 159 venous thromboembolisms (VTEs), found a dose‐dependent relationship between plasma VWF levels and risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The shedding of glycocalicin occurs when GPIb α binds to VWF, followed by the increased glycocalicin content in plasma [ 7 ]. Increased VWF is a risk factor for venous thromboembolism and long-term venous complications [ 27 ]. Microsatellite has been reported as a part of the VWF promoter region and promotes glucocorticoid-induced VWF levels [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…vWF is a clotting factor that is a marker of endothelial dysfunction and is associated with a risk of developing DVT. [70][71][72][73] However, the available data in the studies by Schulman et al 58 and Iding et al 51 suggest there is not an association between vWF-antigen and PTS.…”
Section: General Characteristicsmentioning
confidence: 99%